Methylenetetrahydrofolate Reductase (Mthfr C677T) Gene Polymorphism Effect on Development of Diabetic Nephropathy in Arab Patients with Type 2 Diabetes Mellitus - Khan , Gazala Afreen; Mazen, Shaima; Hamed , Aman Al; Majed, Abir (Bangladesh Journal of Medical Science, 2025)
Background Genetic susceptibility to diabetic nephropathy (DN) has been well-recognized. The enzyme methylenetetrahydrofolate reductase (MTHFR) plays a critical role in homocysteine metabolism. Variations in the MTHFR gene, particularly the C677T variant, have been implicated in the development of macrovascular and microvascular complications. Objectives This study investigates the relationship between the MTHFR C677T genotype and the occurrence of diabetic nephropathy in type 2 diabetes mellitus (T2DM) patients. Methods A total of 50 T2DM patients were analyzed for urinary albumin/creatinine ratio, which was used to classify them into two groups: 26 patients without nephropathy and 24 with nephropathy. Additionally, the study included 30 first-degree relatives (FDRs) of diabetic patients and 20 healthy controls. Diagnostic tests performed included fasting blood glucose, HbA1c, and serum creatinine levels. Plasma total homocysteine levels were measured using a chemiluminescent assay, and the MTHFR C677T polymorphism was analyzed using PCR-restriction fragment length polymorphism (RFLP). Results Among T2DM patients with nephropathy, the distribution of MTHFR genotypes (CC homozygous, CT heterozygous, and TT homozygous) was 20.8%, 54.2%, and 25%, respectively. The T allele frequency was significantly higher in patients with nephropathy (69.2%) compared to those without nephropathy (23.1%), normal controls (26.7%), and FDRs (30%). There was no significant difference in MTHFR genotype or allele frequency between T2DM patients without nephropathy, FDRs, and healthy controls (p < 0.05). The T allele showed a strong association with the development of diabetic nephropathy. Additionally, plasma homocysteine levels were significantly elevated in individuals with TT or CT genotypes compared to those with the CC genotype, with higher levels correlating with the progression of nephropathy. Conclusion The findings suggest that the C677T mutation in the MTHFR gene predisposes T2DM patients to diabetic nephropathy. The presence of the T allele may elevate plasma homocysteine levels, contributing to the progression of nephropathy toward end-stage renal failure. These results highlight the potential role of the MTHFR C677T variant as a genetic marker for susceptibility to diabetic nephropathy in T2DM patients. BJMS, Vol. 24 No. 03 July’25 Page : 799-806